Atom probe tomography characterisation of a laser diode structure grown by molecular beam epitaxy - Bennett, S.; Smeeton, T.; Saxey, David; Smith, G.; Hooper, S.; Heffernan, J.; Humphreys, C.; Oliver, R. (2012)
Atom probe tomography (APT) has been used to achieve three-dimensional characterization of a III-nitride laser diode(LD) structure grown by molecular beam epitaxy(MBE). Four APT data sets have been obtained, with fields of view up to 400 nm in depth and 120 nm in diameter. These data sets contain material from the InGaNquantum well(QW) active region, as well as the surrounding p- and n-doped waveguide and cladding layers, enabling comprehensive study of the structure and composition of the LD structure. Two regions of the same sample, with different average indium contents (18% and 16%) in the QW region, were studied. The APT data are shown to provide easy access to the p-type dopant levels, and the composition of a thin AlGaN barrier layer. Next, the distribution of indium within the InGaNQW was analyzed, to assess any possible inhomogeneity of the distribution of indium (“indium clustering”). No evidence for a statistically significant deviation from a random distribution was found, indicating that these MBE-grown InGaNQWs do not require indium clusters for carrier localization. However, the APT data show steps in the QWinterfaces, leading to well-width fluctuations, which may act to localize carriers. Additionally, the unexpected presence of a small amount (x = 0.005) of indium in a layer grown intentionally as GaN was revealed. Finally, the same statistical method applied to the QW was used to show that the indium distribution within a thick InGaN waveguide layer in the n-doped region did not show any deviation from randomness.